Effectiveness of In–app Advertising on Gen Y’s Attitude and Purchase Intentions - Trivedi, Jay P (Ushus Journal of Business Management, 2015)
Digital marketing is growing at a very fast pace in India. A study by the telecom giant, Ericsson (2014) said Indian users spend three hours and eighteen minutes on an average everyday with their smartphones, of which one-third time is spent on apps. This has given rise to a new ecosystem consisting of many applications and advertising formats. Popular estimates projected by Mobile Marketing Association (2013) had put mobile advertising to touch Rs.430 crores in India by the end of 2014. Gen Y is charting this mobile revolution in India. For a marketer to invest in an advertising medium, it must be effective and affordable. Saladow et al. (2012) opined that more studies have focused on technology related issues of mobile advertising. This research studies the factors (Entertainment, Informativeness and Credibility) influencing the Gen Y’s attitude towards In-application (app) ads; attitude towards brand advertising In-apps and Purchase Intentions thereof. Descriptive research design was used to conduct the research. Statistical analysis was done using Cronbach Alpha, Factor Analysis (EFA and CFA) using SPSS and AMOS 21.0. The hypothesis was verified with the help of structural equation modeling using AMOS 21.0. The results highlight the importance of Entertainment, Informativeness and Credibility in forming positive brand attitudes and Purchase Intentions.